SUSCEPTIBILITY AND DIAGNOSTIC PROTEOMIC BIOMARKERS FOR URINARY SCHISTOSOMIASIS AND ASSOCIATED BLADDER PATHOLOGIES AMONG ADULTS IN EGGUA, OGUN STATE, NIGERIA (2017)
The failure to elicit an adequate immune response to the adult Schistosoma haematobium worm, and continuous strong inflammatory responses to the eggs have been the main causes of bladder pathology in chronic schistosomiasis. The identification of bladder pathology-associated biomarkers is necessary to enable early detection of the disease in a non-invasive manner. The aim of this study was to identify candidate-biomarkers for susceptibility and diagnosis of schistosomiasis and schistosomiasis-associated bladder pathologies in adults. A total of 371 respondents, comprising 130 males and 241 females from Eggua, Ogun State were randomly recruited into a cross sectional study from August 2012 to May 2014. Semi-structured pretested questionnaires were administered to obtain information from consenting respondent. They were screened for S. haematobium ova and bladder pathologies by microscopy and ultrasonography, respectively. Host susceptibility to bladder pathologies and schistosomiasis was determined by Polymerase Chain Reaction genotyping of glutathione-S-transferase (GSTT1 and GSTM1) genes, and Interleukin (IL4 and IL13) genes, respectively. Label-free quantification mass spectrometry-based proteomics approach was used to identify protein biomarkers in the urine. Samples were categorised as Schistosomiasis, Bladder Pathology (BP), Pathology and Schistosomiasis (PS). No Pathology and Schistosomiasis (NPS) served as controls. Descriptive statistics, odds ratios (OR) and Chi-square test were used at α0.05 to determine association between schistosomiasis and bladder pathologies. False Discovery Rate (FDR) analysis was also used to determine significant biomarkers. The mean age of respondents was 48.6 ±0.6 years. The prevalence of schistosomiasis was in 42 (11.4 %) males and 66 (17.9 %) females. Majority (74.1%) had light mean intensity of infection (33.3±0.04 eggs/10mL urine). Bladder pathologies included abnormal bladder wall thickness (29.0%), abnormal bladder shape (7.1%), bladder masses (3.1%) and bladder calcification (2.2%). There was a significant association between urinary schistosomiasis and BP. Respondents with GSTM1 and GSTT1 polymorphisms expressed elevated risks of BP (OR = 4.3, 95% CI 2.0 - 9.2 and OR = 4.2, 95% CI 1.5 – 12.0, respectively); with the PS having more GST polymorphisms than BP. Polymorphisms in IL 4-590 and IL 13-1055 were observed in 24.1% and 9.3% schistosomiasis cases, respectively. The IL 13-1055 polymorphisms did not indicate susceptibility to schistosomiasis in males (OR 0.7, 95% CI 0.3-2.1) but a slight risk was found in females (OR 1.1, 95% CI 0.7-1.7). A total of 1306 proteins and 8752 unique peptides were observed (FDR = 0.01). Human host (54) and parasite-derived (36) potential biomarkers were found for schistosomiasis and associated pathologies. These included new potential biomarkers in schistosomiasis (Sialidase-1, Growth factor 15, Programmed cell death 1 ligand-2) and PS (Arylsulfatase A and Phosphatidylethanolamine-binding protein 4). Candidate proteins were identified for the generation of new diagnostic markers for chronic urinary schistosomiasis and its bladder pathologies.